Preferensi Mahasiswa terhadap Ayam Geprek Bensu sebagai Makanan Ekonomis dan Praktis - Wieke Dwi Sulistianova; Awanda Rohmadona; Syamsul Hidayat (Fakultas Teknik Universitas Maritim AMNI Semarang, 2025)
This study aims to analyze students' preferences for Ayam Geprek Bensu as an economical and practical food option. Data were collected through questionnaires covering various aspects such as consumption frequency, factors influencing choices, and perceptions of taste, price, cleanliness, location, and nutritional value. The results show that most students choose Ayam Geprek Bensu due to its delicious taste (41.2%), easy accessibility (21.6%), and affordable price (18.6%). A total of 57.7% of respondents stated that they would still choose Ayam Geprek Bensu even if other economical food alternatives were available. Factors such as taste, cleanliness, and menu variety were identified as the main priorities in purchasing decisions. However, while the product is considered affordable and filling, respondents expressed mixed views regarding its nutritional value. This study concludes that Ayam Geprek Bensu is a popular choice among students, although there is room for improvement, particularly in menu diversification and enhancing health-related aspects.